Exploration of Influencing Factors for Postoperative Recurrence in Patients with Madelung’s Disease on the Basis of Multivariate Stepwise Cox Regression Analysis - Li S; Xiao Y; Wang Y; Bai M; Du F; Zhang H (Dove Medical Press, 2023)
Shuo Li,* Yiding Xiao,* Yang Wang, Ming Bai, Fengzhou Du, Hailin Zhang Department of Plastic Surgery, Peking Union Medical College Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, People's Republic of China*These authors contributed equally to this workCorrespondence: Hailin Zhang, Email hailin_pumc@126.comPurpose: Madelung's disease (MD) is a rare condition of massive deposits of fat accumulations between superficial and deep fascia at typical locations. There is an absence of systematic studies related to MD in the Chinese cohort. Thus, the objective of the study was to investigate the clinical features of the MD cases in our institution and to explore the clinical variables associated with postoperative recurrence.Materials and Methods: We retrospectively analyzed the clinical information of 21 individuals with MD from 2013 to 2021 enrolled in our institution. The paired t-test and χ2 test were, respectively, used to determine the difference between continuous and classified variables. The univariate Kaplan-Meier analysis by log-rank and multivariate stepwise Cox regression analysis were used to explore variables possibly associated with postoperative recurrence in MD individuals.Results: In the current study, 90.48% of the studied patients were male with a mean age of 48.76 years old. About 61.90% exhibited type I MD. MD patients who experienced postoperative recurrence had a higher age, BMI, incidence of chronic complications, and prevalence of alcoholism than the other MD patients without recurrence (P < 0.05). The univariate Kaplan-Meier analysis by log-rank identified that age, BMI, alcoholism, and comorbidities were influencing factors related with postoperative recurrence (P < 0.05).Conclusion: Demographic characteristics of the 21 studied Chinese cases with MD were generally in accordance with previously published data of other foreign populations. The factors possibly influencing the postoperative recurrence for patients with MD were age, BMI, alcoholism, and a combination of comorbidities. This is the first time that a summarization of clinical characteristics and postoperative recurrence variables of Chinese patients with MD has been reported.Keywords: Madelung's disease, MD, clinicopathological characteristics, recurrence influencing factors, Kaplan-Meier analysis, Cox proportional hazards regression